2018
DOI: 10.1111/add.14403
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of recovery from alcohol use disorder at three years following treatment: can the definition of recovery be extended to include high functioning heavy drinkers?

Abstract: Some individuals who engage in heavy drinking following treatment for alcohol use disorder may function as well as those who are mostly abstinent with respect to psychosocial functioning, employment, life satisfaction and mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
89
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 47 publications
14
89
2
4
Order By: Relevance
“…Heterogeneity was observed in preresolution drinking practices, and drinking practices showed inconsistencies with other risk indicators and had limited utility in predicting outcomes. Functional indicators of alcohol problems, dependence, and reward value showed more consistent associations with different drinking outcomes, which is in line with treatment research indicating that functioning and well-being are important for establishing problem severity and designating outcomes as successful or unsuccessful (e.g., Pearson et al, 2016;Wilson et al, 2016;Witkiewitz et al, 2019). Together, this work suggests that investigation of multiple severity indicators, in addition to drinking practices, will improve prediction of moderation and other outcomes across the drinking problem severity spectrum.…”
Section: Problem Severity Indicatorssupporting
confidence: 82%
See 1 more Smart Citation
“…Heterogeneity was observed in preresolution drinking practices, and drinking practices showed inconsistencies with other risk indicators and had limited utility in predicting outcomes. Functional indicators of alcohol problems, dependence, and reward value showed more consistent associations with different drinking outcomes, which is in line with treatment research indicating that functioning and well-being are important for establishing problem severity and designating outcomes as successful or unsuccessful (e.g., Pearson et al, 2016;Wilson et al, 2016;Witkiewitz et al, 2019). Together, this work suggests that investigation of multiple severity indicators, in addition to drinking practices, will improve prediction of moderation and other outcomes across the drinking problem severity spectrum.…”
Section: Problem Severity Indicatorssupporting
confidence: 82%
“…Such multi‐indicator profiles may aid outcome prediction and ascertain the relative utility of different measures in supporting prognostic judgments and setting drinking goals. Recent treatment studies by Wilson and colleagues () and Witkiewitz and colleagues () found latent profile analysis (LPA) useful for modeling heterogeneity in AUD severity and outcomes based on multiple indicators of alcohol problems, life‐health functioning, and drinking practices. Their LPA results questioned the field’s normative reliance on drinking practices to establish problem severity and treatment success or failure (Falk et al, ), and some outcome profiles indicated improved functioning and reduced alcohol‐related problems without substantial reductions in consumption.…”
mentioning
confidence: 99%
“…Thus, caution should be taken when attempting to broaden the conceptualization of DSM‐5 recovery to include high‐risk drinking based on the findings that asymptomatic and symptomatic high‐risk drinkers had lower odds of AUD severity in terms of numbers of lifetime AUD symptomatology—they may not have been given sufficient time to reach their worst stage of AUD or achieve a stable recovery yet. It is recommended to expand recovery outcome measures to incorporate both physical health consequences and psychosocial functioning and follow up over a longer period of time (Wilson et al., ; Witkiewitz et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, recent empirical work using a data‐driven approach to define recovery has yielded findings that support an expanded definition that includes improved well‐being and functioning. In a secondary analysis of individuals in the outpatient arm of Project MATCH (Project MATCH Research Group, 1997), Witkiewitz and colleagues (2019) found 4 profiles (i.e., subgroups) of individuals defined by measures of alcohol use, alcohol‐related consequences, life satisfaction, and psychosocial functioning 3 years following treatment. These subgroups included: (i) low‐functioning frequent heavy drinkers (15.8%), (ii) low‐functioning infrequent heavy drinkers (16.1%), (iii) high‐functioning heavy drinkers (16.9%), and (iv) high‐functioning infrequent nonheavy drinkers (51.2%).…”
mentioning
confidence: 99%
“…In order to determine the generalizability of these results, we used an independent sample to replicate and extend the Witkiewitz et al’s (2019) findings by examining alcohol‐related outcomes and psychosocial functioning among individuals who completed a 3‐year follow‐up (Zarkin et al, 2008) following participation in the multisite trial of the Combined Pharmacotherapies and Behavioral Interventions for Alcohol Dependence (COMBINE) study (Anton et al, 2006). We hypothesized that a 4‐profile model would be replicated in the COMBINE study data, such that individuals would be classified as low‐functioning frequent heavy drinkers, low‐functioning infrequent heavy drinkers, high‐functioning heavy drinkers, and high‐functioning infrequent nonheavy drinkers at the 3‐year follow‐up.…”
mentioning
confidence: 99%